Essentials of Accident and Emergency Medicine 2019
DOI: 10.5772/intechopen.74123
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound in the Emergency Department

Abstract: Point-of-care ultrasound (POCUS) is a useful diagnostic tool and has become an integral part of the care provided in the Emergency Department. It has evolved over the past two decades to include diagnostic and therapeutic skills. POCUS helps emergency physicians improve their diagnostic accuracy and provide better overall patient care. This chapter will summarize 13 core POCUS applications that are considered within the diagnostic armamentarium of all emergency physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…When comparing our findings with those in the literature, minimal variation was observed in terms of patient volume; however, significant differences were observed with regard to the type of complaints; this is in line with the results of a study conducted in Riyadh, Saudi Arabia [ 12 ]. In contrast with our findings, a study performed at a tertiary hospital in Abu Dhabi reported a significant reduction in ED visits during Ramadan [ 10 ]. We observed a difference between the two countries (UAE and Saudi Arabia) in terms of the extent to which Ramadan changes people's lifestyles and their flexibility and comfort in breaking their fast in hospitals, where oral tablets or IV cannulas are easily available.…”
Section: Discussioncontrasting
confidence: 99%
“…When comparing our findings with those in the literature, minimal variation was observed in terms of patient volume; however, significant differences were observed with regard to the type of complaints; this is in line with the results of a study conducted in Riyadh, Saudi Arabia [ 12 ]. In contrast with our findings, a study performed at a tertiary hospital in Abu Dhabi reported a significant reduction in ED visits during Ramadan [ 10 ]. We observed a difference between the two countries (UAE and Saudi Arabia) in terms of the extent to which Ramadan changes people's lifestyles and their flexibility and comfort in breaking their fast in hospitals, where oral tablets or IV cannulas are easily available.…”
Section: Discussioncontrasting
confidence: 99%
“…7 8 9 10 11 12 13 The salient findings of these and other studies are discussed below. 7 8 9 10 11 12 13 14 15 16 17 18 19 20…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] The salient findings of these and other studies are discussed below. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] One study from Qatar found that Ramadan was not associated with the change in patient age or the proportion of high-acuity cases. However, it was associated with an increase in the proportion of male, pediatric, and Qatari national patient visits.…”
Section: Historical Notementioning
confidence: 99%
See 1 more Smart Citation
“…It even contributes to the management plan by guiding certain procedures. [ 16 17 ] This is particularly important nowadays as PoCUS serves a major role in cost reduction on people and on the health-care system. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%